Analysis Critical Thinking Stage of Eighth Grade in PBL-Scaffolding Setting To Solve Mathematical Problems - Isti, Nur Aisyah; Agoestanto, Arief; Kurniasih, Ary Woro (Department of Mathematics, Universitas Negeri Semarang, 2017)
The purpose of this research was described critical thinking stage of students grade VIII in setting PBL and scaffolding to solve mathematics problems. Critical thinking stage consists of clarification, assesment, inference, and strategy/tactics. The subject were teo students in the level of capacity to think critical (uncritical, less critical, quite critical, and critical). So that this research subject was 8 students in VIII A One State Junior High School of Temanggung. The result showed a description (1) critical thinking stage of students in setting PBL, in clarification the higher level of capacity to think critical students, students can identification information from question fully, can identificatio problem became detailed, and can explored the relationship among the information; (2) a strategy of scaffolding were given by critical thinking stage and TKBK, in assesment, scaffolding had given was given hint/key classically; and (3) transformation characteristic of the critical thinking stage of students after given scaffolding, it because of habituation in setting PBL and scaffolding.